Hydrops fetalis secondary to supradiaphragmatic extrapulmonary sequestration with congenital cystic adenomatoid malformation - S Shukla; H Kini; ML Ilias; K Gautam (Association of Clinical Pathologists of Nepal, 2017)
Congenital cystic adenomatoid malformation is a hamartomatous lesion. A 30 year old woman, G2P1L1, in the 29th week of gestation presented with pain abdomen, chest pain, cough with expectoration, fever and inability to appreciate fetal movements of 2 days duration. Clinically, she had pneumonia. An ultrasound revealed a single fetus in breech presentation with features of hydrops fetalis, hypoplastic left lung, mediastinal shift to the left and poor diastolic and systolic flow in the umbilical artery. A still born male baby delivered subsequently was found at autopsy to have hydrops fetalis, supradiaphragmatic right sided extralobar sequestration with associated congenital cystic adenomatoid malformation.The right lung also showed congenital cystic adenomatoid malformation. There were no other associated anomalies. We present a rare case of extralobar sequestrationwith congenital cystic adenomatoid malformation.